Cenicienta - Filipek, Nina; East, Jacqueline; Mosquera, Raquel (Barcelona : Picarona, 2015)
Once upon a time there lived an unhappy young girl. Her mother was dead and her father had married a widow with two daughters. This is a classic fairy tale of Cinderella.
Translation of: Cinderella.
In Spanish.
Keywords: Cinderella -- (Legendary character) -- Juvenile fiction; Cinderella -- (Legendary character); Fairy tales; Fairy tales; Cenicienta (Personaje legendario) -- Novela juvenil; Cuentos de hadas; Fiction; Juvenile works; 2